Bronze Age Cyprus and the Aegean: ‘exotic currency’ and objects of connectivity - Knapp, A. Bernard (Journal of Greek Archaeology, 2022)
The island of Cyprus is justly regarded as a key juncture in the eastern Mediterranean world, one that played a prominent role in the exchange networks operating within and beyond that region, especially during the Late Bronze Age (LBA). With respect to the Aegean world, contacts are well represented by Aegean and Aegean-style objects and imagery found on the island, a form of ‘exotic currency’ often associated with elite feasting and funerary activities. The arts and crafts of Bronze Age Cyprus are particularly rich in representational terms, particularly evident in the floruit of figurative representations depicted on the pottery, metalwork, ivories and figurines of the LBA. When we focus down onto individual objects or classes of objects, the role of hybridisation practices also seems evident, and any discussion of connectivity between the Aegean world and Cyprus must take such practices into account. The purpose of the present study is to consider a representative example of these objects of connectivity during both the Prehistoric and Protohistoric Bronze Ages, always highlighting the Aegean dimension. In turn, the nature of Aegean-Cypriot relations during and at the end of the LBA is considered with respect to the merchants, mariners, exchange systems and spheres of interaction that characterised Cypro-Aegean connectivity.